Adjustment to disease and quality of life in people with vascular Ehlers-Danlos and Loeys-Dietz syndromes: A mixed-method study - Baeza-Velasco, Carolina; Rodriguez, Nuria; Parra, Laura; Gutiérrez-Rosado, Teresa (Frontiers in Psychology, 2023)
Background: Vascular Ehlers-Danlos (vEDS) and Loeys-Dietz syndromes (LDS) are hereditary disorders of connective tissue having severe vascular complications (HDCTv) which lead to an increased risk of premature death. Little is known about the impact of the disease in patient’s daily life. Method: Sixteen HDCTv patients (vEDS=9 and LDS=7), sixteen age and sex-matched hypermobile Ehlers-Danlos syndrome patients (hEDS) and eighteen healthy subjects (HS), responded to self-questionnaires assessing psychosocial adjustment, quality of life (QoL), anxiety, depression, pain, fatigue and sleep problems. Patients with HDCTv were also interviewed in order to explore qualitatively their experience with the disease. Results: Compared with HS, patients with HDCTv scored significantly higher on anxiety, depression, fatigue, sleep problems, and lower on QoL. Most HDCTv patients (93.8%) have optimal psychosocial adjustment. In addition, HDCTv patients scored higher on QoL and psychosocial adjustment, but lower in pain, fatigue, sleep problems, and depressive symptoms than hEDS patients. Four main themes were identified in qualitative analyses : living with HDCTv, knowledge/ignorance of the disease, health behaviors/self-care and coping strategies. Conclusion: Our results suggest that despite the negative impact of HDCTv on the patients’ daily lives, overall, they present an optimal disease adjustment which points to appropriate coping strategies. More research in psychosocial aspects of people with these rare diseases are needed to confirm these results and better understand their needs.